Pengembangan Model E-Commerce Melalui Rekayasa Proses Bisnis Untuk Penggunaan Modul Voucher Pada Website Rubylicious - Mutiara Yulia (Lembaga Penelitian Universitas Langlangbuana, 2019)
On sales transactions in Rubylicious website is lower than the online sales through the instagram on April to September 2017. So that is necessary to do research about the factors that affect on consumer online purchases. The research aims to understand the consumer interest towards website usages in Rubylicious purchases; design the business process model based on identification result and create the new business development strategy; and build the prototype about the puchases on website. Collecting primary data by in-depth interview with Rubylicious owner and 10 Rubylicious customer. This study focuses on analyzing the customer interest in Rubylicious purchase. Indicators in this research is about the understanding the relevance of consumer’s attitudes with (1) Consumer Online Behavior, (2) Digital Marketing, And (3) Website Purchasing Decision. The result showed that the respondents were satisfied with the product, price, quality and servicing. There are 5 respondents that interest in purchase repeat order in Rubylicious, 4 respondents doubt in purchase repeat order, that need the support factors that can trigger the repeat purchases. 8 respondents interest in promo when purchasing on the website. Coupon voucher for triggering consumer to make purchases via Rubylicious website. Therefore, the modeling the new business process recommendation system using Context Diagram / Data Flow Diagram (DFD) focused on coupon voucher features which is equipped with the prototype design using the opensource e-commerce system tools. In this model system there are six entities, they are: Customer, Web Admin, Finance, Bank, Logistic, and courier. There are three datastores in all levels these are: Product, Customer, Order Data.